Dynamics of the Emergence of Bullying Behavior in Elementary Schools in Manggarai Regency - Bebok, Christin Florentin Meinarty; Eka, Angelina Roida; Danal, Paskaliana; Manggul, Makrina Sedista (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2024)
Previous research has indicated that bullying typically emerges during late childhood, often within elementary school settings. Although bullying behaviors are commonly observed among elementary school children, many students remain unfamiliar with the term